2004
DOI: 10.1364/ao.43.003037
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved multidistance near-infrared spectroscopy of the adult head: intracerebral and extracerebral absorption changes from moments of distribution of times of flight of photons

Abstract: We report on multidistance time-resolved diffuse reflectance spectroscopy of the head of a healthy adult after intravenous administration of a bolus of indocyanine green. Intracerebral and extracerebral changes in absorption are deduced from moments (integral, mean time of flight, and variance) of the distributions of times of flight of photons (DTOFs), recorded simultaneously at four different source-detector separations. We calculate the sensitivity factors converting depth-dependent changes in absorption in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
248
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(266 citation statements)
references
References 25 publications
10
248
1
1
Order By: Relevance
“…scalp skin, subcutaneous tissue, aponeurosis, connective tissue, periosteum, cranium, meninges (dura mater, arachnoid mater, pia mater), cerebrospinal fluid (CSF) (Ellis, 2012)) since the light is both introduced and collected at the surface of the scalp. For a single source-detector arrangement, it was shown the light intensity is~10-20 times (depending on the model for estimating the hemodynamic signals and the SDS) more sensitive to the extracerebral compartment compared to the cerebral compartment (Al-Rawi et al, 2001;Liebert et al, 2004). The tissue-specific energy of light absorbed in the head by using a 3 cm SDS was investigated by Haeussinger et al (2011) by a Monte Carlo simulation based on three-dimensional segmented structural MRI data.…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…scalp skin, subcutaneous tissue, aponeurosis, connective tissue, periosteum, cranium, meninges (dura mater, arachnoid mater, pia mater), cerebrospinal fluid (CSF) (Ellis, 2012)) since the light is both introduced and collected at the surface of the scalp. For a single source-detector arrangement, it was shown the light intensity is~10-20 times (depending on the model for estimating the hemodynamic signals and the SDS) more sensitive to the extracerebral compartment compared to the cerebral compartment (Al-Rawi et al, 2001;Liebert et al, 2004). The tissue-specific energy of light absorbed in the head by using a 3 cm SDS was investigated by Haeussinger et al (2011) by a Monte Carlo simulation based on three-dimensional segmented structural MRI data.…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…TD fNIRS exploits the temporal information encoded in the photon distribution of time-of-flight (DTOF): in particular, in the reflectance geometry where source and collection fibers are placed on the same surface, photons which stay longer in the tissue have a higher probability of exploring deeper regions, while photons that arrive earlier at the detector had very likely traveled only through the more superficial tissue's layers. By applying proper physical models it is then possible to discriminate between the superficial and the deeper contributions to the fNIRS signal [5][6][7][8]. This is of the utmost importance for example in muscle applications where the presence of a superficial adipose tissue may induce large errors in the estimate of the absolute values of O 2 Hb and HHb of the underlying muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new method with a multi-distance probe arrangement based on simulation results has been proposed [38]. The multi-distance FDS [39] and TRS [40], in which diffusion theory is used, have been applied to determine the optical properties of the cerebral tissue in the two-layer head model. Monitoring of oxygen saturation of the cerebral tissue has been performed with spatially resolved spectroscopy [41].…”
Section: Ii) Influence Of the Extracerebral Tissuementioning
confidence: 99%
“…It is still not conclusively established whether the human head can be considered as a homogeneous and/or a simple slab model. Thus, different mathematical approaches, such as deriving the solution of the diffusion equation for multi-layered turbid media [64,65] and analysing moments of the TPSF [40], have been tried. Nevertheless, it has been reported that the estimated m a is nearly equal to the deeper layer m a under the condition where the m a of the upper layer is larger than that of the lower layer in two-layered slab models [49].…”
Section: (A) Time-resolved Spectroscopymentioning
confidence: 99%